TEACHING READING NARRATIVE TEXT THROUGH ONLINE READING STRATEGY - Fitri Novia; Ratna Nery; Indah Lestari (Language and Education Journal, 2023)
The goal of this study was to determine whether eighth graders at SMP PGRI Pedamaran who received instruction in the online reading strategy differed significantly from those who did not in their reading comprehension abilities. A quasi-experimental design was implemented for this study. The data was obtained through a written test consisting of multiple-choice questions. T-test was applied to the data for analysis. Based on the findings of the independent sample t-test, it was determined that the Pvalue (0.000) was less than the value (0.05) and the t-test obtained (2.917) was greater than the t-table (2.00). The results pointed out that alternative hypotheses were found to be accepted whereas null hypotheses were found to be rejected. The students who were taught by applying Online Reading Strategy and those who were not showed a significant difference in their reading comprehension achievement. In other words, SMP PGRI Pedamaran eighth grade students' reading comprehension performance was enhanced by employing an online reading strategy